Mosaic disease in chilli (Capsicum annuum) cv Kalimpong Local in Darjeeling hills of West Bengal and its management - R.P. PANT and Y.S. AHLAWAT, K.K. BISWAS*, K.B. PUN (Indian Phytopathology, 2005)
The symptoms of chilli mosaic diseare in the cv Kalimpong Local popularly known as Dolo Kursani in hill regions of Darjeeling District of West Bengal and Sikkim state include green to yellow mosaic, mottling of leaves with or without deformation, stunting and extremely deformed shoe string leaf in advanced stages of the disease. Incidence of the disease ranged from 5- 100% with low incidence of higher altitude. The virus was mechanically transmitted to solanaceous and cruciferous hosts, chilli, tobacco, radish and rye. In electron microscope, negatively stained preparations from naturally infected leaf samples revealed the presence of two types of virus particles, one similar to Cucumber mosaic cucumovirus (CMV) and other similar to Potato virus Y (PVY). Both single and mixed infections of these viruses were confirmed by EM decoration test and DAC-ELISA. Field experiment revealed that planting of crop in the month of March reduces disease incidence thereby increasing yield. Application of NPK with or without systemic insecticides at 15- 20 days interval reduced disease incidence and increased the yield by 82 to 90%.